Sistem Informasi Geografis Pemetaan Jembatan Berbasis Web - Ade Sutedi; Latifah Latifah; Pazar Ahmad Alawi (Jurnal Algoritma, 2023)
The bridge is part of the means of transportation to connect two areas that are separated by a river, ravine, or other. Garut Regency is one of the areas in West Java Province which has a large area and is connected by many bridges. These bridges are managed by the Department of Public Works and Spatial Planning (PUPR), specifically the Bina Marga sector. To support the management of bridges in Garut Regency, a system is needed that can inform the location and condition of the bridge. This geographic information system will provide information to the user regarding the map of the bridge location, bridge name, road sections, dimensions, type, photo, and condition of the bridge. The purpose of this study is to design a geographic information system for mapping bridges using the Rational Unified Process (RUP) development methodology with Unified Modeling Language (UML) modeling. The results of the study show that the geographic information system built can map the location and inform the details and condition of the existing bridges in Garut Regency. Then, the results of the Likert scale calculations from the questionnaires distributed to respondents from PUPR Garut district obtained an assessment of 96% which indicates that this system is acceptable and can be implemented for a bridge mapping system.